Pendidikan Karakter di TK Pertiwi Batang Gansal (Studi Kualitatif) - Wasiah Wasiah; Yuni Resiyati; Supatmi Supatmi (LPPI Yayasan Almahmudi bin Dahlan, 2023)
Character education is moral education, character, values, character that aims to develop the ability of students to make good and bad decisions, as well as maintain the good and realize that goodness in everyday life wholeheartedly, based on the explanation above it is also known that teachers need to provide good character for children. This study uses a type of research with data collection in a natural setting, using natural methods, and conducted by a naturally interested researcher or researcher. In qualitative research, data collection is carried out in natural settings (natural conditions), primary data sources, and data collection techniques. The techniques for collecting this data consist of: Interview, Observation and Documentation. Data analysis is qualitative in nature described by words or sentences separated by category to obtain conclusions. Based on the results of research on